Haben HIV-Positive eine besondere Verantwortung?: Ein Diskussionsbeitrag - Staub, Roger (Bundesgesundheitsblatt Gesundheitsforschung Gesundheitsschutz, 2007)
In the 1980s, most Western countries decided to opt for a new public health approach based on learning strategies to fight HIV/AIDS. Within the new public health paradigm, every sexually active person protects him-/herself, whereas it is the infected people that bear the burden of prevention according to old public health. The paper begins with a clear statement for the new public health approach that includes self-protection and the protection of civil rights. It argues that this approach is still valid under the changing circumstances due to combination therapies and the developments related to them, such as the introduction of routine HIV screening in some countries. On this background, the paper examines from an ethical perspective to what extent people with HIV have a responsibility in HIV prevention. The paper argues that a person with HIV has a responsibility to protect his/her partner in the case of a relationship of love. On the other hand, in the case of "purely" sexual encounters, each person is responsible for his/her own security and should not rely on the other. This position also helps to clarify prevention messages. In conclusion, the paper shows how morality evolves into ethical positions and then translates into the law. It finally claims for stronger obligations for sex businesses to support HIV prevention.